Polymers in cell encapsulation from an enveloped cell perspective_ - De Vos, P.; Lazarjani, H. A.; Poncelet, D.; Faas, M. M.
In the past two decades, many polymers have been proposed for producing immunoprotective capsules. Examples include the natural polymers alginate, agarose, chitosan, cellulose, collagen, and xanthan and synthetic polymers poly(ethylene glycol), polyvinyl alcohol, polyurethane, poly(ether-sulfone), polypropylene, sodium polystyrene sulfate, and polyacrylate poly(acrylonitrile-sodium methallylsulfonate). The biocompatibility of these polymers is discussed in terms of tissue responses in both the host and matrix to accommodate the functional survival of the cells. Cells should grow and function in the polymer network as adequately as in their natural environment. This is critical when therapeutic cells from scarce cadaveric donors are considered, such as pancreatic islets. Additionally, the cell mass in capsules is discussed from the perspective of emerging new insights into the release of so-called danger-associated molecular pattern molecules by clumps of necrotic therapeutic cells. We conclude that despite two decades of intensive research, drawing conclusions about which polymer is most adequate for clinical application is still difficult. This is because of the lack of documentation on critical information, such as the composition of the polymer, the presence or absence of confounding factors that induce immune responses, toxicity to enveloped cells, and the permeability of the polymer network. Only alginate has been studied extensively and currently qualifies for application. This review also discusses critical issues that are not directly related to polymers and are not discussed in the other reviews in this issue, such as the functional performance of encapsulated cells in vivo. Physiological endocrine responses may indeed not be expected because of the many barriers that the metabolites encounter when traveling from the blood stream to the enveloped cells and back to circulation. However, despite these diffusion barriers, many studies have shown optimal regulation, allowing us to conclude that encapsulated grafts do not always follow nature's course but are still a possible solution for many endocrine disorders for which the minute-to-minute regulation of metabolites is mandatory.
Keywords: ALGINATE; BIOCOMPATIBILITY; BIOTOLERABILITY; ENCAPSULATION; INSULIN; NATURAL POLYMERS; PEG; SURFACE PROPERTIES; SYNTHETIC POLYMERS